High-quality binary amplitude hologram generation for digital micromirror device based holographic display (2025)
In this work, we demonstrate a high-performance binary amplitude hologram generation method and verify its performance with an experimental holographic projection scheme based on binary amplitude modulation by means of a digital micromirror device. The proposed method consists of a subsampling procedure applied to a target scene prior to hologram generation with binarized stochastic gradient descent (B-SGD). In combination with temporal multiplexing, this approach leads to holographic reconstructions with significantly improved quality when compared to direct application of the B-SGD and other common binary amplitude hologram generation methods. Furthermore, our proposal achieves this improved quality with nearly the same computational speed as the conventional B-SGD. Numerical results confirm the validity of our proposal, and an experimental holographic projection scheme is implemented to demonstrate its feasibility.